Development and validation of a Malay version questionnaire for assessing risk perception of type 2 diabetes (RPDM). - Miaw Yn Jane Ling; Norfazilah Ahmad; Mohd Firdaus Mohd Radi; Azimatun Noor Aizuddin (PLoS ONE)
Background The burden of type 2 diabetes is increasing globally. Risk perception of type 2 diabetes plays an important role in motivating adoption of healthy lifestyle and preventive health interventions. To address the increasing burden of type 2 diabetes in Malaysia, a better understanding on its risk perception is needed as a guide for preventive interventions. This study was aimed at developing and validating a Malay-language questionnaire to assess the risk perception of type 2 diabetes (RPDM) among Malaysians. Methods The questionnaire (RPDM) was developed based on the Health Belief Model and previous literature. A 59-item question pool was initially developed, reviewed by experts for content validity and pretested on five respondents. Different samples were used for pilot study (n = 100) and subsequent validation study (n = 158). Exploratory factor analysis (EFA) and Confirmatory factor analysis (CFA) were used to evaluate construct validity and construct reliability of the questionnaire. Results The EFA yielded five-factors model, including 48 items with good factor loadings of > 0.40. CFA was carried out using item parceling. The final model shows acceptable model fit and had sufficient convergent and discriminant validity. The value of construct reliability ranged between 0.76 and 0.90. Conclusion This newly developed and validated Malay-language RPDM questionnaire is valid and reliable for measuring the five constructs (perceived self-efficacy, perceived severity, perceived benefit, perceived susceptibility and perceived barrier) of risk perception of type 2 diabetes among Malaysians. This Malay-language questionnaire may contribute to a better understanding of risk perception of type 2 diabetes among Malaysians, as well as enhancement of diabetes prevention communication between healthcare providers and their clients.